Research, Design and Ergonomics: a panorama related to the post graduation program in Design (UFMA) - Diniz, Raimundo Lopes; Lima, André Luís de Oliveira; Viana, Thiscianne Mesquita (DAT Journal, 2021)
This paper presents a description related to the creation, implementation and current context of the research line “Design: ergonomics and usability of products and systems”, as part of the consolidation process of the post Graduate Program in design of the Federal University of Maranhão in its historical panorama. A concept, goals and structural elements (as curriculum, professors, dissertations, laboratories and research groups) are presented.